Identity and acculturation: interethnic relations in the Basque Autonomous Community - Larrañaga, Nekane; Garcia, Iñaki; Azurmendi, Maria-Jose; Bourhis, Richard (Journal of multilingual and multicultural development, 2016)
This study analyses the influence of ethnic identity on the acculturation orientations of Basque undergraduates, towards groups in traditional contact (native Basques and native Spaniards) and towards recent immigrant groups. Five dimensions were used to measure the Basque and/or Spanish identities: linguistic, cultural, political, global, and the desire to be Basque and/or Spanish. Two factors were identified by analysing the factor structure of the items: Basque and Spanish identity. The scales of both factors were dichotomised using the mid-point of a 7-point Likert-type scale. The subjects were classified, according to their scores on identity scales, into three prototypes: two polarised identities, Basque and Spanish, and a third Dual prototype merges both identities. The main aim is to compare the host acculturation orientations of the three prototype identities towards different groups. The differences in acculturation were small in regard to immigrant groups, although orientations were more negative towards groups of immigrants who are less highly regarded by the host society. Interestingly, the prototypes differ in the acculturation orientations regarding the groups in traditional contact, the native Basques and native Spaniards. An in-group favouritism effect occurs, in both polarised prototypes, whereas the Dual prototype shows similar positive acculturation orientations towards both groups.